2014 IEEE 9th IberoAmerican Congress on Sensors 2014
DOI: 10.1109/ibersensor.2014.6995525
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone controlled platform for point-of-care diagnosis of infectious diseases

Abstract: In this work, we present the development of a point-of-care platform for the serologic diagnosis of infectious diseases. The complete system consists of magnetic particles with immobilized antigens, disposable electrochemical cells, hardware and software. The main purpose of this paper is to present the last two components. The platform is powered by a rechargeable battery and can be controlled using mobile devices, allowing point-of-care diagnosis of diseases. The platform was successfully tested for the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…1c. Details on the electronic instrumentation are given elsewhere [13]. The working electrode potential was set at -280 mV and the resulting current was recorded during 60 s; this potential value is negative enough to produce the reduction of 1,4 benzoquinone under diffusion-controlled conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…1c. Details on the electronic instrumentation are given elsewhere [13]. The working electrode potential was set at -280 mV and the resulting current was recorded during 60 s; this potential value is negative enough to produce the reduction of 1,4 benzoquinone under diffusion-controlled conditions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical measurements were carried out at 25 °C in 50 μL of a PBS buffer of pH 7, 0.1 M KCl, 4 mM hydroquinone (redox mediator), and 1.5 mM H 2 O 2 . A portable potentiostat Nanopoc [17] was used for the amperometric measurements (Figure 1c). Potentials were measured and referred to in the text against a Ag|AgCl|0.1 M KCl reference electrode.…”
Section: Methodsmentioning
confidence: 99%
“…Sun et al tried two different potentiostat sets to optimize the smartphone-based CV measurements with three electrodes . Then, Salomon et al reported a multichannel amperometric platform, which provided a high-throughput screening method for serologic diagnosis of infectious diseases (Salomon et al, 2014).…”
Section: Amperometric Biosensors On Smartphonementioning
confidence: 99%